A Qualitative Study on Employee Experiences in Indonesian Service Organizations: Understanding Drivers of Organizational Citizenship Behavior (OCB) - Muhammad Arya Bhagaskara (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This research examines the dynamics of Organizational Citizenship Behavior (OCB) among employees in a public-service organization in Indonesia, emphasizing the influence of leadership support, employee engagement, and organizational culture on voluntary behaviors that exceed formal job expectations. Employing a qualitative methodology through semi-structured interviews with ten employees from various functional units, the study reveals intricate insights into the psychological and organizational precursors of Organizational Citizenship Behavior (OCB). The thematic analysis identifies three principal themes: (1) leaders’ supportive behaviors that enhance emotional security and motivation; (2) employees’ inherent sense of responsibility and collective orientation; and (3) organizational cultural norms that prioritize collaboration, trust, and mutual assistance. Results show that OCB is not just a personal trait; it is also shaped by how people interact with each other and the rules that govern the workplace. Human resource managers should strengthen relational leadership practices, set up recognition systems that value discretionary contributions, and promote a culture of collaboration to keep OCB levels high, according to practical implications. This study adds to the body of research by giving a detailed qualitative picture of OCB in Indonesian public organizations, which is an area that has not been studied enough in the past.